Asymptotic expansivity - Lee K. (2022)
KL was partially supported by NRF grant No. 2018R1A2B3001457 . CAM was partially supported by CNPq -Brazil No. 307776/2019-0 and the NRF Brain Pool Grant No. 2020H1D3A2A01085417 . HV was partially supported by Universidad Nacional de Ingeniería P-CC-2021-000666 , FC-PF-33-2021 and Fondecyt-Concytec contract 100-2018 .